IEEE GRSS Mato Grosso do Sul (Brazil) Student Branch Chapter: 2020 Activities [Chapters] - Estrabis N.V. (2022)
© 2013 IEEE.The Federal University of Mato Grosso do Sul (UFMS) IEEE Geoscience and Remote Sensing Society (GRSS) Student Branch Chapter, also known as MS GRSS IEEE Student Chapter, is located in Mato Grosso do Sul State, Brazil. The Chapter represents a partnership of students and researchers from two labs: the Geomatics Lab at UFMS and the Inovisão Lab at Catholic Dom Bosco University (UCDB). The advisors are Prof. José Marcato Junior and Prof. Hemerson Pistori. The 2020 administrative organization is presented in Figure 1.